2016
DOI: 10.1007/s11060-016-2189-7
|View full text |Cite
|
Sign up to set email alerts
|

A molecular biology and phase II study of imetelstat (GRN163L) in children with recurrent or refractory central nervous system malignancies: a pediatric brain tumor consortium study

Abstract: Telomerase activation is critical in many cancers including central nervous system (CNS) tumors. Imetelstat is an oligonucleotide that binds to the template region of the RNA component of telomerase, inhibiting its enzymatic activity. We conducted a molecular biology (MB) and phase II study to estimate inhibition of tumor telomerase activity and sustained responses by imetelstat in children with recurrent CNS malignancies. In the MB study, patients with recurrent medulloblastoma, high-grade glioma (HGG) or epe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 20 publications
1
52
0
1
Order By: Relevance
“…Imetelstat, an antisense oligonucleotide that inhibits telomerase by binding to TERC , is the only telomerase‐targeting drug that has been evaluated in phase II clinical trials of brain tumors . Although telomerase inhibition was observed, no objective response of imetelstat was achieved in refractory pediatric brain tumors . An inherent problem of targeting telomerase is that the inhibition of telomerase in a cancer cell already having elongated telomeres would not yield an immediate anti–proliferative effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imetelstat, an antisense oligonucleotide that inhibits telomerase by binding to TERC , is the only telomerase‐targeting drug that has been evaluated in phase II clinical trials of brain tumors . Although telomerase inhibition was observed, no objective response of imetelstat was achieved in refractory pediatric brain tumors . An inherent problem of targeting telomerase is that the inhibition of telomerase in a cancer cell already having elongated telomeres would not yield an immediate anti–proliferative effect.…”
Section: Introductionmentioning
confidence: 99%
“…18 Although telomerase inhibition was observed, no objective response of imetelstat was achieved in refractory pediatric brain tumors. 19 An inherent problem of targeting telomerase is that the inhibition of telomerase in a cancer cell already having elongated telomeres would not yield an immediate anti-proliferative effect. Telomerase inhibition may also lead to the activation of alternative lengthening of telomeres (ALT), a homologous recombination-based telomerase-independent telomere elongation mechanism, which would abrogate the effects of telomerase-targeting anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 42 patients were enrolled, and evaluable patients experienced a 95% reduction in telomerase activity; however, no objective tumor responses were observed. In addition, two patients died of intratumoral hemorrhage secondary to thrombocytopenia, leading to the end of this study . In another phase II study, patients with advanced NSCLC developed neutropenia and thrombocytopenia treatment with GRN163L, and no improvement in PFS was observed in these patients .…”
Section: Oligonucleotides Targeting Telomeres and Telomerasementioning
confidence: 88%
“…In other words, the length of time required to shorten the telomere length significantly affected the usage of GRN163L in a clinical setting, and has rendered the drug most useful in cases where telomeres are already shortened . Studies on patients with advanced non–small‐cell lung cancer (NSCLC) showed only limited efficacy, and in pediatric patients with brain cancer GRN163L (Imetelstat) was only able to be administered for an average of 13 days (a 6‐to‐21‐day range) before intolerable toxicity levels characterized by platelet nadir being established . Moreover, GRN163L drug holidays, due to these increased toxicities, lead to rapid reestablishment of telomere length and continuing cell growth .…”
Section: Telomerasementioning
confidence: 99%